Bringing Back Ho'okipa: Engaging Tourism for Sustainable Self-determination in the Pacific - Fa'anunu, Angela I (ProQuest Dissertations & Theses, 2015)
This research investigated how some indigenous ‘āina (land)-based Native Hawaiian organizations engage with tourism strategically to enable them to continue working towards sustainable self-determination in Hawai‘i. This research was explored through the experience of the Ka Welina Network made up of organizations who adopted a community-based host-visitor (CBHV) model that emphasized the sharing of meaningful experiences, guided by the traditional customs of ho‘okipa (hosting), such as reciprocity, kuleana (responsibility), malama (to take care) and aloha (love). This research investigated the challenges that the organizations faced in implementing the values-based model within a predominant capitalist society highlighting how cultural practitioners must deal with the business of generating revenue to sustain organizational survival, while also remaining true to their Native Hawaiian values, goals, and way of life, aims that are often at odds with each other. Data were collected through participant observations, “talk-story” qualitative interviews, and secondary data. Research findings point to conditions under which hosted experiences may lead to transformations among visitors that contribute to host communities’ goals towards sustainable self-determination. Based on the case study analysis, a conceptual model of values-based host-visitor engagement is offered. Keywords: self-determination, values-based tourism, community planning, sovereignty, sustainability, sustainable tourism, ho‘okipa